SARS-CoV-2 Bound Human Serum Albumin and Systemic Septic Shock - Johnson, Andrew S.; Fatemi, Rouholah; Winlow, William (Frontiers in Cardiovascular Medicine, 2020)
The emergence of the Covid-19 virus and the subsequent pandemic have driven a great deal of research activity. The action of Covid-19 are caused by the severe respiratory syndrome coronavirus 2 (SARS-CoV-2) and it is the underlying actions of SARs-CoV-2 virions on the endothelial glycocalyx that we consider here. One of the key factors in coovid-19 infection is its almost unique age-related profile, with a doubling in mortality every 10 years after the age of 50. The endothelial glycocalyx layer is essential in maintaining normal fluid homeostasis, but is fragile and prone to pathophysiological damage. It is physiologically significant in capillary microcirculation and in fluid distribution to the tissues. Human serum albumin (HSA), the most abundant protein in plasma, is created in the liver which also maintains its concentration, but this reduces by 10-15% after 50 years of age. HSA transports hormones, free fatty acids and maintains oncotic pressure, but SARS-CoV-2 virions bind competitively to HAS diminishing its normal transport function. Furthermore, hypoalbuminemia is frequently observed in patients with such conditions as diabetes, hypertension and chronic heart failure, i.e. those most vulnerable to SARS-CoV-2 infection. Acute respiratory stress syndrome (ARDS) occurs when fluids build-up in the alveoli and it is associated with sepsis, whose mechanism is systemic, being associated with the fluid and logistic mechanisms of the circulation. Glycocalyx damage is associated with changes plasma protein concentration, particularly HSA and blockage of albumin transport can produce the systemic symptoms seen in SARS-CoV-2 infection and sepsis. We therefore conclude that albumin binding to SARS-CoV-2 virions may inhibit the formation of the endothelial glycocalyx by inhibition of albumin transport binding sites. We postulate that albumin therapy to replace bound albumin might alleviate some of the symptoms leading to sepsis and that clinical trials to test this postulation should be initiated as a matter of urgency.